Facts and Figures about Hydropower Development in Nepal - Shrestha, Hari Man (Hydro Nepal: Journal of Water, Energy and Environment, 2017)
The author in this paper makes efforts to present facts and figures about hydropower development in Nepal. The paper also highlights that interest groups play differently at different times, but the decision makers must be fair and be bold enough to decide correctly in a way favorable to the need of the country. The paper also states that the country’s hydropower requirement should be the priority focus for its development by way of attracting its nationals in capacity building through self-study, self-finance, self-construction and self-consumption. It is, however, disgusting to note that even the most attractive simple type of moderate size projects needed to be kept for such purpose has been handed over to the outsiders for use outside the country, e.g. the Upper Karnali and Arun-3 projects. Such approach is leading to a situation that Nepal in the future will have to buy her own resources at higher prices from the outsiders. HYDRO Nepal Journal Journal of Water Energy and Environment Issue: 20 Page: 1-5